Determinan Niat untuk Melakukan Whistleblowing pada Pemerintah Daerah - Yesi Mutia Basri; Merri Agustin; Edfan Darlis (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
This study aims to determine the factors that influence the intentions of government employees to do withlowing. This research examines Effect of personal cost of reporting, level of seriousness of fraud, organizational commitment and professional commitment on the intention to do whistleblowing. The population in this study were all staff / employees at OPD Kuantan Singingi. The sampling method used in this study was the purposive sampling and using the sample of 72  civil servants from 24 different OPD. The results of  regression analysis  show that personal cost affects the intention to do whistleblowing. 2) the level of seriousness of fraud affects the intention to do whistleblowing. 3)  organizational commitment affects the intention to do whistleblowing. 4)  professional commitment affects the intention to do whistleblowing. This research has a contribution in reducing fraud in government